Evolution of a Research Landscape: A Bibliometric Analysis of Harmful Cultural Practices in Nepal (2016-2025) - Khadka, Kalpana (NPRC Journal of Multidisciplinary Research, 2025)
Background: Harmful cultural practices (HCPs) in Nepal, such as Chhaupadi (menstrual seclusion), child marriage, dowry-related violence, and witchcraft accusations, persist as significant social problems with severe consequences for health, education, and human rights. Despite legal bans and interventions, deeply rooted social norms hinder full behavioural change. The research landscape on these practices is fragmented across public health, legal, and social-anthropological disciplines, creating a need for a systematic analysis of the evidence base.Objective: This study aimed to map and analyse the evolution of the research landscape on HCPs in Nepal from 2016 to 2025 using bibliometric techniques. The objective was to identify temporal trends, disciplinary emphases, leading institutions, geographic collaborations, and persistent research gaps.Methods: A bibliometric analysis was conducted on literature published between 2016 and 2025. Data were retrieved from Dimensions.ai, PubMed, Google Scholar, and NepJOL using a standardized Boolean search string. Inclusion criteria focused on peer-reviewed articles in English or Nepali (with English abstracts) addressing HCPs in Nepal. After deduplication and cleaning in EndNote 21 and Excel, the final corpus was analysed using VOSviewer for network visualization and Excel for descriptive statistics.Findings: The analysis revealed a steady increase in annual publications, peaking at 27 in 2024, indicating growing scholarly attention. Citations also rose markedly, reaching a peak of 302 in 2024, signifying the field's growing academic influence. Nepal and the United States were the leading contributors (35 publications each), with strong international collaboration networks. Tribhuvan University was the most productive institution (22 documents), while Pokhara University's publications had notably high citation impact. Key research themes identified included Chhaupadi, child marriage, and gender-based violence, with a focus on health, legal, and socio-cultural dimensions.Conclusion: Research on HCPs in Nepal has expanded significantly over the past decade, maturing into an internationally recognized and interdisciplinary field. The findings confirm that while scholarly output and impact are growing, the evidence base remains uneven, with some practices and regions receiving more attention than others.Implication: This bibliometric map provides a valuable resource for researchers, funders, and policymakers to identify influential works, understand collaboration patterns, and pinpoint under-researched areas. Future efforts should prioritize cross-disciplinary studies and community-led, culturally sensitive interventions to effectively address persistent harmful cultural practices.